Analisis Modal Sosial Sebagai Prediktor Berbagi Pengetahuan Tacit Pada Wirausaha Di Kabupaten Gresik - Khoirur Rozaq (Jurnal Publikasi Ilmu Manajemen, 2022)
Social capital is a strong network in the form of relationships between individuals that develop over time, trust and collective action within an organization arise. The level of social capital owned by company employees or business people can affect the transfer of knowledge, especially in establishing relationships and collaborating with business partners to develop their own business which will ultimately affect innovative work behavior. The purpose of this study was to determine the effect of social capital on the sharing of tacit knowledge and its effect on the ability to innovate. The population in this study are 2 company employees and 2 business actors. Methods of data collection using observation and interviews. The analytical method used is descriptive analysis. The results showed that social capital had a significant positive effect on knowledge transfer and innovative work behavior.